(untitled) (Third Sector Social Economic Review, 2020)
Increasing the differences between regionals are creating a serious policy concern in modern-day Turkey. Differences such as increased regional inequalities, increased polarization tendency, and deterioration of income distribution will cause many problems in economic, financial, political, and social areas. To overcome these problems, regional problems should be analyzed well and studies should be done to ensure regional development. In this framework, incentive policies are used as an important fiscal policy tool. It is aimed to solve the existing problems by investing in regions that are lagging in various fields with the incentives. In the study, incentive policies are discussed in the regional development axis and the current situation is evaluated for public finance. Various indicators at the level of financial, political, demographic, foreign trade, employment, and education categories are been collected to evaluate the incentive policies of Nomenclature of Territorial Units for Statistics of Turkey - 2 (NUTS-2) regions. The WASPAS method is used to evaluate the total of 13 indicators of the 26 regions in different categories from 2018. The findings show that the regions that can be qualified as developed are in the upper ranks, while the relatively underdeveloped regions are in the lower ranks. Thanks to the results, the suggestions are made for the solution of the missing and failing aspects of the system.